Endoscopic Treatments in Perforation or Fistula in Upper Gastrointestinal Tract - Sun Gyo Lim (Yong Chan Lee, 2024)
Perforations or fistulas in the gastrointestinal tract constitute serious emergencies and are associated with high morbidity and mortality rates. Such lesions, occurring in the esophagus, stomach, and duodenum, may arise from noniatrogenic causes (e.g., peptic ulcers, corrosive insults, trauma, malignant tumors) and iatrogenic causes (e.g., endoscopic procedures and surgeries). A prompt diagnosis and an appropriate management strategy are crucial for early recovery before secondary complications occur that may be induced by infection and/or chemical damage from gastric acid or bile. Various endoscopy-based treatment modalities have been developed and play pivotal roles in the management of upper gastrointestinal perforations and fistulas. Through-the-scope clips, self-expanding metallic stents, over-the-scope clips, endoscopic suturing devices, and endoscopic vacuum therapy have significantly improved the success rates associated with treating these types of lesions. However, choosing the optimal modalities that lead to good patient prognoses depends on the lesion characteristics, such as its size, duration, location, and surrounding tissue condition. Thus, gastrointestinal endoscopists have to regularly master and incorporate new endoscopy-based treatment approaches for these complicated conditions.